Severity Assessment, Prognostication and Risk Stratification Using Apache II and CECT in Cases of Severe Acute Pancreatitis in Prospective Study - Dr. Tarun Kumar Naik, Dr. Manish Kumar Khare,; Devedi, Dr. M.K.; Gupta, Dr. Madhusoodan (International Journal of Innovative Research in Medical Science, 2017)
Purpose: - The present to grade the severity of severe acute pancreatitis using APACHE II scoring, the severity using CECT abdomen, the utility of each as prognostic indicator in Severe Acute Pancreatitis, the prognosis and stratify the risk using both APACHE II and CECT for management of the patient admitted at Chandulal Chandrakar Memorial Medical College and Hospital Kachandur, Durg. Methods: - This prospective study was carried out on patients hospitalized for acute pancreatitis in the surgery department of Chandulal Chandrakar Memorial Medical College Kachandur, Durg. A total of 50 patients with the diagnosis of acute pancreatitis admitted between Jan 2015 to June 2017 were included in the study, out of these 50 patients 36 patients had severe acute pancreatitis and 14 patients had mild acute pancreatitis Patients with history of treatment elsewhere, recurrent episodes in the past were excluded from the study. Patients enrolled in the study were subjected to the study design viz; ongoing APACHE II assessment, CECT on 72 hrs and CECT on 15th day. However certain patients were in the study who could not be subjected to all the 3 parameter because of death / deranged RFT or irregular follow up. Results and Conclusion: - Correlation between APACHE II within 48 hours of admission and Contrast enhanced CT Scan of abdomen in 72 hours had the sensitivity of 78.57% and specificity of 88.89%. Correlation between APACHE II within 48 hours of admission and Contrast enhanced CT Scan of abdomen on 15th day was better with 85.19% sensitivity and 88.89% specificity. Patients with an APACHE II Score of 8 or more within 48 hours of admission had a severe course with a mortality rate of 32.72 % compared to nil mortality rates in those with APACHE II Score < 8. The ease and accuracy of APACHE II Scoring System identified that subset of patients who had Severe Acute Pancreatitis and thereby needed intensive care. Patients with APACHE II score of 8 or more are likely to develop loco-regional complications of pancreatitis like sterile pancreatic necrosis, infected necrosis or WOPN.